MENGENAL BAHAYA ADIKSI GADGET DAN CARA MENGATASINYA - Yunita, Mutiara Mirah; Lesmana, Teguh; Jatmika, Devi; Damayanti, Alfina; Kusuma, Theresia Finda (Universitas Bunda Mulia, 2021)
The use of gadgets is nothing new for teenagers. Through gadgets, teenagers can seek information, connect with friends and seek entertainment. BPS Indonesia stated that the development of cellular phone users in Indonesia increased to around 65.53% (341.28 million subscribers) in 2019, which previously only reached 38.05% in 2010. Moreover, during the Covid-19 pandemic, In this regard, the use of gadgets as a means of work and schooling has also increased drastically, both in terms of users and in terms of duration of use. Excessive use of gadgets can cause negative impacts, some of which are stress and symptoms of gadget addiction. Through this service activity, a series of events starts on Friday, April 16, 2021 at 13.00 - 15.00 WIB using the online method via google meet which is divided into three sessions, starting with a brief survey on the use of gadgets by participants, material sessions about gadgets, stress, gadget addiction, and how to deal with the addiction, and finally the question and answer session. The results of this service received a pretty good response and participants experienced an increase in understanding of this gadget addiction. The hope is that the results of this dedication can improve adolescents' understanding of the relationship between stress and gadget use, gadget addiction and how to deal with gadget addiction.